Do All Coronary Anomalies Need to Be Fixed? - M. Praveen; Rakesh Yadav (Journal of the Practice of Cardiovascular Sciences)
Coronary anomalies are rare. Management of anomalous coronary origin depends on various features which are determined by a CT coronary angiography usually. This case report highlights an important feature that needs to be considered before CT coronary angiography which guides the management of anomalous origin of coronary arteries.